2014
DOI: 10.1111/hpb.12189
|View full text |Cite
|
Sign up to set email alerts
|

Management of incidental and suspicious gallbladder cancer: focus on early referral to a tertiary centre

Abstract: The majority of patients with incidental gallbladder cancer were not amenable to further potentially curative resection. The radiological suspicion of gallbladder cancer should lead to prompt referral to a tertiary hepatobiliary unit for further management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 32 publications
(45 reference statements)
2
21
0
1
Order By: Relevance
“…The proportion of patients with unresectable advanced disease at reoperation varies, but the systematic review by Choi and colleagues reported an overall pooled rate of 23 per cent. Some recent studies from the UK suggest the unresectability rate is twice as high, at about 50 per cent.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…The proportion of patients with unresectable advanced disease at reoperation varies, but the systematic review by Choi and colleagues reported an overall pooled rate of 23 per cent. Some recent studies from the UK suggest the unresectability rate is twice as high, at about 50 per cent.…”
Section: Resultsmentioning
confidence: 98%
“…However, there are few data to support a need for an emergency referral and immediate redo surgery if an incidental cancer is detected, although the timing of surgery remains debated. In several studies, the unresectability rate at restaging (before redo surgery) is as high as 50 per cent for incidental cancers, despite early referral. Indeed, in one study early referral was a strong predictor of unresectability.…”
Section: Resultsmentioning
confidence: 99%
“…Prompt surgical treatment of such patients with segment 4b/5 hepatectomy and portal lymph node dissection may confer a comparable survival benefit to initial radical cholecystectomy . However, time from cholecystectomy to referral has been shown to be a negative prognostic factor, as many patients will be unresectable at the time of evaluation by a specialist . The optimal time between operations has been estimated to be 4‐8 weeks to minimize interval disease progression .…”
Section: Discussionmentioning
confidence: 99%
“…Survival outcomes have been shown to depend on surgical strategy, pathologic stage, comorbidities, and experience of the surgical unit. 3 …”
Section: Introductionmentioning
confidence: 99%